Recurrent abdominal pain in children in Wuhu, China was not associated with Helicobacter pylori infection, but associated with <1 h/day physical activity and academic stress - Bai, Xiaohui; Cao, Huiru; Zhu, Liuming; Wu, Xiaomin; Wang, Guixiang; Yu, Wenchao; Gu, Yong (Frontiers in Pediatrics, 2024)
Background: Recurrent abdominal pain ( RAP ) is one of the most common gastrointestinal disorders in children. The aim of this study was to investigate the relationship between RAP and Helicobacter pylori infection in children in Wuhu, China as well as the risk factors for Helicobacter pylori infection in this region.In this cross-sectional survey, we randomly selected children aged 6-17 years who underwent health examinations at three public hospital examination centers in Wuhu city, Anhui Province, China. Helicobacter pylori infection was assessed by a 13 C-urea breath test (UBT) kit. Questionnaires were custom designed to obtain data on behavioral, sociodemographic, and environmental characteristics, and to investigate the relationship between RAP and Helicobacter pylori infection in children.Results: A total of 1,187 children aged 6-17 years were enrolled, among these children, 182 were diagnosed with RAP, with an incidence rate of 15.3%. A total of 266 children were infected with Helicobacter pylori, with an infection rate of 22.4%. Multivariate regression analysis revealed that physical activity for ˂1 h/d and academic stress are associated with RAP in children, whereas Helicobacter pylori infection, age, sex, body mass index (BMI), and fast-food consumption are not associated with RAP in children. Our research also found that the risk of Helicobacter pylori infection increases with age in children. Risk factors for Helicobacter pylori infection in children include leftbehind children, poor hygiene habits, family history of Helicobacter pylori infection, and mother with low cultural levels.Helicobacter pylori infection, but strongly associated with ˂1 h/d physical activity and academic stress.